International Comparison of Children’s Knowledge, Barriers and Reported Fluid Intake Across the School Day. - Tara, Coppinger; Kristy, Howells (International Journal of Nutrition, 2019)
Background To date, no research has explicitly examined children’s knowledge and consumption of fluids at school, particularly during times of exercise (physical education (PE)). Methods Between May and July, 2018, 322 (213 females, 104 males; mean age = 8 years 5 months, SD ± 2 years 1 month) elementary school children from Ireland (n=237) and England (n=85) completed a questionnaire on their understanding of fluid intake and how much they perceived they drank on days when they did/did not participate in PE. Results Younger (<9 years) English children were most thirsty at the end of the school (68%), compared to younger and older (≥9 years) Irish children who were most thirsty after (38% <9 years; 39% ≥9 years) or during (21% < 9 years; 21% ≥9 years) PE. In both countries for <9 year olds, similar amounts were consumed on days when they did, and did not, partake in PE with 41% of all participants reporting intakes below daily guidelines. No child, of any age, was correct at predicting what their fluid intake should be on days when they took part in PE. Conclusion Young children in England and Ireland do not understand fluid recommendations, especially the increased need for fluid on days when they partake in PE. Further objective research is needed to ascertain whether actual fluid intake in children matches perceived intakes and whether the structure of the school day, and intensity levels of PE lessons, influence these intakes. Additional research needs to gauge the importance of the teacher and how they are a key influencer in supporting children in their learning of how, why and when to drink.
Keywords: Fluid intake; Children; School; Physical Education